NATIONAL CHARACTER AND PERCEPTION IN THE SHORT STORIES OF M.MAGAUIN (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
The article describes the national traits and perceptions of the main characters in Mağauin's short stories. The core of the works reflects the wisdom and lifestyle of the Kazakh people, with the writer’s skill in harmonizing the stories with the people of that nation. The article concludes with a discussion on how national character and perception are reflected in various issues. It argues that in literary studies, the concept of the historical foundation of a literary work doesn’t mean taking historical events at face value, but rather revitalizing the good qualities stored in a nation's memory. Examples are provided to prove this point. The writer is said to elevate the typical actions of leaders from Kazakh villages during the Soviet era into an artistic detail. The article also emphasizes that the writer doesn’t dwell on the ‘positive’ or ‘negative’ character types common in Socialist realism, instead unveiling artistic images through the development of the narrative. В этой статье исследуется взаимосвязь национального характера и познания в рассказах.The writer brings forth the spirit of the Alash leaders, portraying them through characters, and shows how they start to lose their national character, perception, and moral compass. The article is intended for researchers and literary scholars.